2022
DOI: 10.1590/fst.29322
|View full text |Cite
|
Sign up to set email alerts
|

Bran characteristics impact the whole wheat noodle quality

Abstract: Ten hard wheat varieties, including five each red (Huai mai 35, Ningmai 13, Yang mai 20, Su mai 188 and Ji mai 22), and white winter (Yang mai 23, Hao mai 1, Annong 0711, E mai 596 and Zheng mai 7698) varieties harvested in May 2019 were kindly provided by School of Agronomy of Anhui Agricultural University, China. Commercial noodle wheat flour (protein content 12.2%, moisture 14%) was provided by Fengzheng Food Company (Weifang, China) Bran powder preparationWheat grains were tempered 24 h to 16% moisture and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Similarly, Wang et al . (2022) showed that by adding wheat bran to noodles, the resistance to cooking and adhesiveness of the products increased.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Wang et al . (2022) showed that by adding wheat bran to noodles, the resistance to cooking and adhesiveness of the products increased.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, soluble polyphenols do not react with other molecules physically or chemically, and can be extracted by traditional polar water/organic solvents (Călinoiu & Vodnar, 2018). However, insoluble-bound phenols are usually combined with plant cell wall polysaccharides in the form of ester bonds or covalent bonds, so it is not easy to extract them by traditional methods, resulting in the difficulty of effective utilization of these highly active substances (Wang et al, 2022b). In recent years, more and more studies have shown that the content and antioxidant activity of insoluble-bound phenols in wheat bran are higher than those of soluble polyphenols (Mazahir et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Starch is one of the most important commodities in the world, playing an important role in many fields, among which the composition and functional changes of glutinous rice starch have a great impact on its industrial application (Thitisaksakul et al, 2021). Gelatinization and rejuvenation of starch can form gels with a certain network structure, whose texture qualities such as hardness, elasticity and chewiness have an important impact on the food quality of related products (Xie et al, 2022;Wang et al, 2022). During the industrial production of glutinous rice flour by food enterprises, in order to achieve the purpose of sterilization and rapid drying, the high temperature treatment at 180 °C will lead to the pre-gelatinization of starch (Tian et al, 2022).…”
Section: Introductionmentioning
confidence: 99%